The dark side of global integration: Increasing tail dependence - Beine, Michel; Cosma, Antonio; Vermeulen, Robert (Journal of Banking & Finance, 2010)
We measure stock market coexceedances using the methodology of Cappiello, Gerard and Manganelli (2005, ECB Working Paper 501). This method enables us to measure comovement at each point of the return distribution. First, we construct annual coexceedance probabilities for both lower and upper tail return quantiles using daily data from 1974–2006. Next, we explain these probabilities in a panel gravity model framework. Results show that macroeconomic variables asymmetrically impact stock market comovement across the return distribution. Financial liberalization significantly increases left tail comovement, whereas trade integration significantly increases comovement across all quantiles. Decreasing exchange rate volatility results in increasing lower tail comovement. The introduction of the euro increases comovement across the entire return distribution, thereby significantly reducing the benefits of portfolio diversification within the euro area.